Research methods in international relations - Lamont, Christopher (SAGE Publications Ltd [2022], 2022)
The only guide to conducting research in International Relations. Covering the full breadth of methods in IR with unrivalled clarity, this best-selling textbook takes you through the entire process of doing research, from honing your question to writing up the dissertation. The engaging and jargon-free style demystifies the process of doing research, whilst helping you develop a comprehensive understanding of the strengths and limitations of different methods and methodologies.